2018
DOI: 10.1007/s10266-018-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Generation and histomorphometric evaluation of a novel fluvastatin-containing poly(lactic-co-glycolic acid) membrane for guided bone regeneration

Abstract: The purpose of this study was to evaluate the effects of a poly(lactic-co-glycolic acid) (PLGA) membrane containing fluvastatin on bone regeneration at bone defects in rat calvaria and tibia for possible use as a guided bone regeneration (GBR) membrane. PLGA and fluvastatin-containing PLGA (PLGA-fluvastatin) membranes were prepared and mechanical properties were evaluated. Standardized bony defects were created in rat calvaria and the right tibia, and covered with a PLGA or PLGA-fluvastatin membrane. Bone rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In our previous study, PLGA membranes loaded with FS were implanted on rat calvaria to increase their ability to regenerate new bone formation, especially in the initial period of healing. However, we found that only minimal bone had formed underneath this membrane, and the PLGA membrane had almost degraded after 8 weeks of healing time [ 23 ]. Despite the necessity of a second-stage surgical procedure for membrane removal, TMs may overcome the limitations of degradable membranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, PLGA membranes loaded with FS were implanted on rat calvaria to increase their ability to regenerate new bone formation, especially in the initial period of healing. However, we found that only minimal bone had formed underneath this membrane, and the PLGA membrane had almost degraded after 8 weeks of healing time [ 23 ]. Despite the necessity of a second-stage surgical procedure for membrane removal, TMs may overcome the limitations of degradable membranes.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA membrane loaded with or without FS was fabricated as described in a previous report [ 23 ]. In short, to prepare a single-phase solution, 2.4 g of PLGA was dissolved in 3 ml dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using fluvastatin-loaded PLGA membranes, Zhang and coworkers were able to show enhanced bone formation in both a rat calvarial and tibial defect model after 4 and 8 weeks. According to the authors, the PLGA membranes released fluvastatin with a release rate of approximately 1 µg/day [75]. Nevertheless, designed smart scaffolds potentially ought to comprise both natural and synthetic polymers to fulfill all requirements.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Among them, Sr shows beneficial effects on bone cells and for bone formation in vivo and for osteogenic differentiation at low doses [44,45,46,47,48,49,50,51]. Another approach to provide occlusive GTR membranes with the ability to regenerate bone is the incorporation of growth factors, drugs or other biomolecules [5,52,53]. However, the physical adsorption of biomolecules on polymeric membranes has the drawbacks of low immobilization efficiency and fast desorption which make their covalent bonding on the polymer necessary [53].…”
Section: Introductionmentioning
confidence: 99%